MENAKAR DETERMINAN KINERJA KARYAWAN - Baskoro, Arbi Leo; Widowati, Sri Yuni; Santoso, Aprih (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2019)
The population in this study were all marketing employees of PT. Borobudur Oto Mobil which amounted to 36 employees and the sampling technique used in this study  was the census  method  and  the analysis  tool  used  in  this  study  was multiple linear regression. The regression test results show that the variables of work facilities, leadership, competence and division of labor have a positive effect on employee performance and the results of hypothesis testing indicate that the variables of work facilities, leadership, competence and division of labor have a significant effect on employee performance. The results of the determination test produce the adjusted R square value in the regression model obtained at 0.610 which means that 61 percent of employee performance variables can be explained by variables of work facilities, leadership, competence and division of labor and the results of the accuracy test table obtained 0,000 smaller than 0, 05 which means that employee performance variables can be jointly explained by leadership variables, work facilities, competencies and division of labor.